Analisis Beban Ledakan Dan Pengaruhnya Terhadap Struktur Portal Baja - Joni, Mustika; Suryanita, Reni; Kamaldi, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bomb explosions in Indonesia have occured relatively more frequently and become a real threat to society. In the blast phenomena, loss of life and injuries to occupants can result from the structural collapse. Therefore it were necessary to do an analysis of the effect under blast load on the building with the aim of this research was to analyze the condition of the frame on a structure based on analysis of internal forces and structural response due to blast load. The building structure model was a steel frame structure of 5 story with a typical floor to floor height of 4 m. Variations of explosive weights of 500 kg and 1.000 kg of TNT were applied to a building structure model have converted into a static load at distance 25 m of blast source. To define the blast load on the structure, ATBLAST software will be used, and to determine blast load parameters need to be calculated with Pythagoras Theorem based on TM 5-1300-1990. Analysis was performed with Finite Element Method (FEM) software with linier static method will be used, the results of analysis were axial and moment force. The axial force was 621,28 kN, moment force weakness axis direction was -665,93 kN-m and moment force strong axis direction was 0,48 kN-m. Based on this analyze it can be concluded that the internal forces have occured proportional to the explosive weights of the building structure and frame conditions in the structure model was considered still allowable to received blast load of 500 kg TNT, however for the 1.000 kg of TNT explosive weights, structure model was collapse.Keywords: Blast load, inform force, linier static